Dylan's magic cards - De Pierres, Marianne; Sulzer, Anne (Macmillan Education Australia South Yarra [Vic.], 1999)
Dylan's Magic Cards by Marianne De Pierres is an enchanting children's book that follows the adventures of a young boy named Dylan, who discovers a set of magical cards that bring his imagination to life. Each card holds a unique power, allowing Dylan to embark on exciting quests and face challenges in a fantastical world. As he navigates this magical realm, Dylan learns valuable lessons about bravery, friendship, and the importance of believing in oneself. The story is filled with vibrant illustrations and imaginative scenarios, captivating young readers and encouraging them to explore the wonders of creativity and the magic of storytelling.